Does Experience Matter? Innovations and the Productivity of ICT in German Services - Thomas Hempell (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2002)
In this paper, it is argued that ICT investment is closely linked with complementary innovations and most productive in firms with innovative experience. In an analysis based on firm?level panel data covering the period 1994?99, system GMM estimates for an extended production function framework reveal significant productivity effects of ICT in the German service sector. Moreover, there is strong support for the hypothesis that the experience gained from past process innovations is a specific feature that makes ICT investment more productive. The results suggest that ICT may have been contributing to productivity differentials between firms.
Keywords: C23; D24; L80; O32; 330; Productivity; Information and Communication Technologies; Innovation; Services; Panel Data; Computergestütztes Verfahren; Informationstechnik; Produktivität; Innovation; Lernprozeß; New Economy; Dienstleistungssektor; Schätzung; Unternehmensdienstleistung; Deutschland